1997
DOI: 10.1038/sj.mp.4000300
|View full text |Cite
|
Sign up to set email alerts
|

Restrained eating is associated with low leptin levels in underweight females

Abstract: best tool available for the psychometric assessment of restrained eating. 9 Psychometrically defined restrained Restrained eating is eaters consume less energy, take fewer meals and show higher preference for low calorie foods than unreassociated with low leptin strained eaters. 10 Restrained eaters have a lower energy expenditure than unrestrained females of comparable levels in underweight lean body mass. 11 Ovarial dysfunction occurs more frequently in restrained female eaters. 12 Dietary restraint females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 0 publications
0
19
3
Order By: Relevance
“…9,10,27,28 Furthermore, the results do not support the hypothesis that in eating disordered and in BED patients a low serum leptin concentration is a primary phenomenon, which causes a restriction of food intake in anorexia nervosa patients, 27 or an increased hunger sensation that compels bulimia nervosa or BED patients to binge. 29 Rather, increased or decreased serum leptin concentrations merely seem to be the consequence of prolonged periods of sharply negative energy balance ensuing from frequent dieting in anorectic patients or in restricting individuals, or of frequent bouts of positive energy balances due to bingeing episodes in BED and in bulimic patients.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…9,10,27,28 Furthermore, the results do not support the hypothesis that in eating disordered and in BED patients a low serum leptin concentration is a primary phenomenon, which causes a restriction of food intake in anorexia nervosa patients, 27 or an increased hunger sensation that compels bulimia nervosa or BED patients to binge. 29 Rather, increased or decreased serum leptin concentrations merely seem to be the consequence of prolonged periods of sharply negative energy balance ensuing from frequent dieting in anorectic patients or in restricting individuals, or of frequent bouts of positive energy balances due to bingeing episodes in BED and in bulimic patients.…”
Section: Discussioncontrasting
confidence: 52%
“…9,10,27,28 In contrast, this study showed that serum leptin concentration was positively related only to scores indicating a tendency to lose control over food intake. This would suggest that the dietary restraint of severely obese patients is inadequate in reducing the current food intake and therefore plays no role in influencing leptin concentration.…”
Section: Discussioncontrasting
confidence: 48%
“…First, in over 400 male and female students with a BMI below 85% average body weight, most individuals were healthy 27,28 (Hebebrand et al, unpublished data) and tracking of BMI in adulthood 29 implies that many lean young adults will remain so over time. These individuals can also expect a longer life span than those with higher body weight.…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…26 Fourth, serum leptin levels also differentiate between constitutionally lean females and those with AN. 27,28 Fifth, initially at least, weight loss in AN is usually voluntary, and although intentional weight loss is moderately heritable, the majority of genetic factors affecting BMI are different from those affecting intentional weight loss. 35 Molecular genetic studies that incorporated relevant covariates into linkage analyses have included the related construct of minimum BMI, a variable that more closely approximates the core phenotype of AN as it indexes the extreme low BMI values reached as the body experiences a complete failure to regulate weight.…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…20,23 The relationship between dietary restraint and endogenous leptin levels has been studied in overweight women, but no significant correlation was found. 24,25 To our knowledge, this relationship has not yet been investigated in overweight men. The question remains whether pharmacological treatment, that is, PEG-OB protein treatment, replaces or supports an increase of dietary restraint during treatment.…”
Section: Introductionmentioning
confidence: 98%